An Assistance to Develop Learning Materials Based on Video Analysis and Virtual Laboratories for Physics MGMP Teachers in Padang Pariaman District - Zulhendri Kamus (Pelita Eksakta, 2019)
Teachers for physics subjects is an avant garde of the best quality learning in a class, especially the schools at Padang Pariaman Regency. In consequence, the teacher must have the reliable professional competencies, namely the abilities and skills to develop teaching materials that are in accordance with student characteristics and contextual (based on natural phenomena in the environment). In fact, physics teachers have not been able to develop the teaching materials that compatible with student and contextual. The purpose of an assistance program is to become the abilities and skills of teachers to develop teaching materials based on video analysis of physical phenomena and virtual laboratories. There are several methods used in realizing the objectives of the activity, namely presentation, discussion and practice. Presentations are used to provide knowledge and insight to teachers about teaching materials, physical phenomena videos, video analysis and virtual laboratories. Group and class discussions are conducted to address the problems of teachers both theoretically and practically. The teacher does to design, develop and produce physics phenomena videos, video analysis, virtual laboratories and teaching materials by using practical methods. There are seven results and outcomes of an assistance program, namely 11 Student Worksheets as teaching materials, 5 videos about physical phenomena, 5 virtual laboratories, the results of test about developing teaching materials with very good categories, the response of participants about an assistance program with good to very good categories, the implementation of student worksheets products in learning can improve student activities and suggestions from participants about the importance of follow-up activities.